(untitled) (Journal of Medicine, 2015)
This prospective cross sectional study was conducted in Dhaka Medical College Hospital, Dhaka during July, 2013 to December, 2013. Hundred patients were included in this study. Peptic ulcer disease, presented as upper abdominal pain is one of the common disease with a number of underlying causes. Prospective analyses of 100 patients with upper abdominal pain were studied at medicine units of Dhaka Medical College Hospital, Dhaka. Of these 36 patients belonged to peptic ulcer, 20 patients to irritable bowel syndrome and 22 patients to non-ulcer dyspepsia. Next in order were helminthiasis (5 patients), cholelithiasis (4 patients), gastric carcinoma (4 patients), liver abscess (5 patients) chronic pancreatitis (3 patients) and acute pancreatitis (1 patient). Mean age incidence in this series was 39.47 years. Male and female ratio was 1.54:1. Forty patients were smoker with male and female ratio of 3.44:1.All patients had presenting feature of upper abdominal pain. Commonest site of pain was in the epigastrium in 48.08% of cases.Pain was burning in 43.27% cases, periodic pain in 24.03%, and nocturnal hunger pain in 33.65% of cases.Relief of pain after taking food were observed in 38.46%. Epigastric tenderness was present in 56.73% patients.The diagnosis of peptic ulcer disease, irritable bowel syndrome and non-ulcer dyspepsia, the three leading causes of upper abdominal pain, were suspected by history and physical examination but it was difficult to interpret these on clinical ground alone .Some routine and some selected investigation were done for confirmatory diagnosis. In this series, significant disparity detected between clinically diagnosed peptic ulcer diseases 90.38% and endoscopically confirmed peptic ulcer disease, 34.62% cases. As a consequence of wrong diagnosis of PUD, there are huge misuses of ulcer healing drugs and a great economic burden on patients (300 taka per month) and on the nation. DOI: http://dx.doi.org/10.3329/jom.v16i1.22386 J MEDICINE 2015; 16 : 27-34